Strategi Metakognitif dalam Pembelajaran: Tinjauan Sistematis dan Implikasinya terhadap Pemahaman Konsep Matematika - Nina, Kartina; Hendro, Prasetyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article examines metacognitive strategies in understanding mathematical concepts through a Systematic Literature Review (SLR) approach to eleven scientific articles published between 2018 and 2024. This study focuses on the application of metacognitive strategies that include planning, monitoring, and self-evaluation at various levels of education. The results of the analysis indicate a consistent positive influence on four main aspects, namely: (1) understanding of mathematical concepts, and (2) the role of teachers in implementing metacognitive strategies. Although most studies support the effectiveness of this strategy, one study shows different findings that emphasize the importance of the teacher's role in optimizing implementation. These findings underscore the need to integrate metacognitive strategies into conceptual understanding in classroom learning practices and open up opportunities for further research, especially regarding long-term impacts and adaptive application in various learning contexts.